2019
DOI: 10.3390/molecules24244460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Hybrids Targeting Opioid and Neurokinin Receptors

Abstract: Morphine, which acts through opioid receptors, is one of the most efficient analgesics for the alleviation of severe pain. However, its usefulness is limited by serious side effects, including analgesic tolerance, constipation, and dependence liability. The growing awareness that multifunctional ligands which simultaneously activate two or more targets may produce a more desirable drug profile than selectively targeted compounds has created an opportunity for a new approach to developing more effective medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Recently, Wtorek et al reported a series of hybrids based on a cyclic opioid peptide and linear peptide NK1 agonist/antagonist fragments [ 23 ]. One of these NK1R-antagonist-containing compounds was shown to be effective in acute pain model and not to trigger tolerance development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Wtorek et al reported a series of hybrids based on a cyclic opioid peptide and linear peptide NK1 agonist/antagonist fragments [ 23 ]. One of these NK1R-antagonist-containing compounds was shown to be effective in acute pain model and not to trigger tolerance development.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of gastrointestinal transit impairment was touched upon only a few times in the context of hybrid opioid/antitachykinin compounds. The aforementioned work by Wtorek et al demonstrated that their opioid/antitachykinin ligand did not produce constipation [ 23 ]. Earlier, Largent-Milnes et al reported that compound TY027 exerted no influence on gastrointestinal transit [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another bivalent combination in which the hydrazide bridge found application was in hybrids of opioid agonist and neurokinin-1 receptor (NK1R) antagonists [27,28]. The rationale for preparing such multitarget compounds consisting of opioid sequences along with the pharmacophoric elements required for targeting some other receptors stems from the fact that simultaneous modulation of a few receptors involved in pain perception can provide analgesic compounds with enhanced efficacy and fewer side effects [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence on the heteromerization of native opioid receptors in discrete brain neuronal circuits with selective targeting of heteromers as a tool to modulate receptor activity, and multifunctional ligands, which simultaneously activate two or more targets to produce a more desirable drug profile, are emerging concepts for the development of novel therapeutic drugs and strategies, presented in the earlier cited report [2] and in two additional research articles [13,14].…”
mentioning
confidence: 99%